An Alternative Framing of Organ Donation Registration: The Collective Donor Behavioral Model. (June 2021) - Tinning, Emma; Bednall, Timothy C.; Bove, Liliana L.; Jordan, Helen
Notwithstanding the prevalent use of donor registration prediction models grounded by the theory of planned behavior (TPB), registration behavior continues to remain low. A collective donor behavior (CDB) model underpinned by social exchange theory is introduced and its predictive ability is tested against a baseline TPB model using an online survey of adults ( n  = 1, 055). Individuals who indicated they were not registered donors were contacted 3 months later to track their registration status. The CDB model was found to explain 45% of variance in registration intentions which was comparable in performance to TPB. Normative commitment was found to be strongly associated with registration intentions, and both institutional trust and trust in others fostered this commitment. The CDB model provides different insights on how to increase donor registration intentions. Namely, interventions need to facilitate individual positive experiences with institutions such as hospitals and strengthen social inclusion perceptions.